Analysis of Cross-border Payment Regulation and its Impact on Consumers in Indonesia - Rahman, Arif; Darmawan, Didit; Saputra, Rio (Metromedia, 2024)
This research discusses the legal challenges in the regulation of cross-border electronic payments in Indonesia, with a focus on protecting the rights of users using foreign platforms. Although Law No. 11 Year 2008 on Indonesian Electronic Information and Transactions Law provides the legal basis for electronic transactions in Indonesia, it is still insufficient to protect consumers in cross-border transactions. The absence of specific regulations leads to legal uncertainty and increased risk of financial loss for users. In addition, limited supervision by Bank of Indonesia of foreign platforms operating in Indonesia adds to the challenge of creating a safe and reliable payment system. The research also highlights the importance of specific regulations that require foreign platforms to comply with data security and consumer protection standards, as well as the government's role in international collaboration to create better protections. The findings of this study provide policy recommendations to strengthen the regulation and supervision of cross-border payments in Indonesia.